Speed development in swimmers: Total condition training - Goldsmith, W.; Pyne, D.
This article examines three approaches to the development of speed in all swimmers and outlines their coaching and scientific rationale. We then introduce the concept of total condition training, which has the aim of maximising both speed and endurance. Several features of this model are discussed in detail and relevant suggestions on developing speed in swimmers are presented. The three common approaches used for the development of speed in swimmers are: 1. High Volume and High Intensity Training (Broken Egg Coaching) 2.Specific Energy System Training 3.Total Condition Training The pros and cons as well as the features of total condition training for speed are discussed.